Efficacy of Gensini Score in Assessing the Severity of Coronary Artery Disease (Academia Journal of Medicine, 2020)
Background: The present study was conducted to assess the efficacy of the Gensini score in the severity of CAD. Subjects & Methods: 100 hospitalized patients presenting as myocardial infarction (MI) (STEMI and NSTEMI), CAD without MI (CSA and UA) were recruited for the study. Plasma 25-OH Vit D level was measured by using the electrochemiluminesent immunoassay (ECLIA) method. Gensini score was recorded which was based on the percentage of luminal narrowing (25%: 1 point; 50%: 2 points; 75%: 4 points; 90%: 8 points; 99%: 16 points, and total occlusion: 32 points). Results: Severe vitamin D deficiency < 20ng/ml is seen in a total of 17 patients, out of which 9 patients were having SVD, 8 patients were having DVD, none of the patients having TVD and Normal Coronaries. Gensini score is calculated in all patients undergoing CAG. Mean Gensini score for DVD 34.75, for SVD 16. The mean vitamin D levels are correlated with the severity of coronary disease using the Gensini score. There is a trend towards increasing severity of coronary artery disease with decreasing levels of vitamin D levels with an odd ratio of 2.233. Conclusion: Authors found that Gensini score is useful in assessing severity of Coronary artery disease.
Keywords: Coronary artery disease; Gensini score; Vitamin D